(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The thesis devotes to the role of Irony in the production of speech in both languages, English, Uzbek. As for the definition of irony, is the use of words that have a different meaning than what you truly mean to express, often to offend or irritate someone or merely for laughs.